Identification of the wave speed and the second viscosity of cavitation flows with 2D RANS computations - Part I. (November 2015) - Decaix, J; Alligné, S; Nicolet, C; Avellan, F; Münch, C
Abstract: 1D hydro-electric models are useful to predict dynamic behaviour of hydro-power plants. Regarding vortex rope and cavitation surge in Francis turbines, the 1D models require some inputs that can be provided by numerical simulations. In this paper, a 2D cavitating Venturi is considered. URANS computations are performed to investigate the dynamic behaviour of the cavitation sheet depending on the frequency variation of the outlet pressure. The results are used to calibrate and to assess the reliability of the 1D models.